2006
DOI: 10.1007/s00595-006-3261-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Prognostic Index Influences Patient Outcome for Node-Positive Breast Cancer

Abstract: These five genes might play an important role in deciding the behavior of node-positive breast cancer. The PI system could thus predict the prognosis of node-positive breast cancer, and might therefore be able to provide valuable information for the prognosis of breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…However, in this study, only implicated in soft tissue sarcomas, leukemia, astrocytoma and in cancers of the breast, prostate, lung, liver and esophagus. [2][3][4][5][6][7][8][9][10] Decreased expression of LATS2 is seen in prostate cancer tissues, 7 and levels of phosphorylated LATS1/LATS2 are reduced in tumor susceptible mst1/2 liver-specific knockout mice. 9 Classically, tumor suppressor loss-of-function occurs through mutations.…”
Section: Role Of Lats As Tumor Suppressormentioning
confidence: 99%
See 2 more Smart Citations
“…However, in this study, only implicated in soft tissue sarcomas, leukemia, astrocytoma and in cancers of the breast, prostate, lung, liver and esophagus. [2][3][4][5][6][7][8][9][10] Decreased expression of LATS2 is seen in prostate cancer tissues, 7 and levels of phosphorylated LATS1/LATS2 are reduced in tumor susceptible mst1/2 liver-specific knockout mice. 9 Classically, tumor suppressor loss-of-function occurs through mutations.…”
Section: Role Of Lats As Tumor Suppressormentioning
confidence: 99%
“…As such, loss of either of these genes leads to malignant phenotypes. [2][3][4][5][6][7][8][9][10] Therefore, understanding how LATS1 and LATS2 operate is key to understanding tumorigenesis. This review will explore what we know about how these tumor suppressors function, both as individual proteins and collectively, highlighting their potential redundant or distinct roles.…”
Section: A New Governor Of Cellular Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Because the stomach is also of foregut origin, the high frequency of LOH at the IRX1 locus in gastric cancer suggested that the IRX1 gene may be involved in the development of gastric cancer. Asaka et al (2006) reported that IRX3 is downregulated in breast cancer patients with shorter survival times. IRX3 was also downregulated in androgen-insensitive prostate cancer cell lines (Zhao et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of LASP1 in the breast cancer cell lines BT-20 and MCF-7, and the ovarian cancer cell line SKOV-3 has however been demonstrated to result in strong inhibition of proliferation and migration (13,14). In 2006, LASP1 was identified as one of 5 genes down-regulated in poor prognosis, lymph-node-positive breast cancer (15). LASP1 has also been identified as a potential p53 (a tumour suppressor) target in hepatocellular carcinoma, with further work suggesting that p53 may play a role in influencing tumour metastasis through LASP1 (16).…”
Section: Introductionmentioning
confidence: 99%